Weathering a demand shock: The impact of prior vertical scope on post‐shock firm response - Lim, Najoung; Kim, Seojin; Agarwal, Rajshree (Strategic Management Journal, 2023)
Abstract Research Summary We examine how and why pre‐existing vertical scope may cause differences in product market exit rates after sudden and exogenous decreases in demand. Our empirical context is the U.S. medical diagnostic imaging industry (2004–2009), wherein a major Medicare reform created a derived demand shock to equipment manufacturers. Using a difference‐in‐difference‐in‐difference design, we find integrated firms were more likely to exit than nonintegrated firms. Building on the literature conceptualizing firms' pre‐shock vertical scope as a representation of existing resources and governance choices, we explain that integrated and nonintegrated firms responded differently by leveraging their own distinctive capabilities. Our qualitative insights suggest that higher market exit of integrated firms was driven by their higher adjustment costs due to frictions across strategies for demand management versus cost reduction. Managerial Summary This study investigates whether having a dedicated sales force or utilizing third‐party distributors can help mitigate the adverse effect of an abrupt demand decrease on manufacturers. In the context of the US medical imaging equipment industry affected by the 2005 Deficit Reduction Act, we show that all firms implemented strategies for demand management, cost reduction, and product portfolio reconfiguration in response. Manufacturers using external distributors experienced fewer frictions across these strategies than those with an internal sales force and were less likely to exit. Thus, a firms' vertical scope can impact how they cope with environmental changes.